"It didn't make me a better teacher": inservice teacher constructions of dilemmas in high-stakes teacher evaluation. Issue 4 (2nd October 2019) - Warren, Amber N.; Ward, Natalia A.
ABSTRACT: This article explores how inservice teachers articulate and challenge notions of effective teaching as part of an environment of high-stakes teacher evaluation (HSTE) in Tennessee. Drawing on data from public forum speeches at school board meetings, policy documents, and interviews, we used thematic discourse analysis to investigate how teacher effectiveness is discursively constructed by teachers. Findings demonstrate how participants drew upon competing definitions of effective teaching to build a discursive case for potential areas for improvement regarding the observation of teaching as part of HSTE policies. Because measures of teacher performance are an issue of much debate in the United States, teachers' descriptions of the relationships between teaching evaluations, observations, professional development, and student learning are critical to understanding how to develop effective procedures for observation and evaluation. Implications for developing evaluation informed by teachers' experiences are discussed.